2022
DOI: 10.3389/fimmu.2022.839380
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab and Active Antibody-Mediated Rejection in Kidney Transplantation: A Literature Review

Abstract: IntroductionChronic kidney disease (CKD) is a major public-health problem that increases the risk of end-stage kidney disease (ESKD), cardiovascular diseases, and other complications. Kidney transplantation is a renal-replacement therapy that offers better survival compared to dialysis. Antibody-mediated rejection (ABMR) is a significant complication following kidney transplantation: it contributes to both short- and long-term injury. The standard-of-care (SOC) therapy combines plasmapheresis and Intravenous I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Subsequently, there have been many other reports demonstrating benefits in treatment of AMR, cAMR, and CMR with tocilizumab in adult and pediatric kidney transplant patients. Treatment of AMR/cAMR with long‐term administration of tocilizumab had been overall safe and without significant side effects in our hands 30–36 . A recent report by Cabezas et al 35 evaluated the reported an evaluation of published literature from case studies regarding the efficacy of tocilizumab in treating cAMR.…”
Section: Tocilizumab (Anti–il‐6r) For Treatment Of Amrmentioning
confidence: 77%
See 3 more Smart Citations
“…Subsequently, there have been many other reports demonstrating benefits in treatment of AMR, cAMR, and CMR with tocilizumab in adult and pediatric kidney transplant patients. Treatment of AMR/cAMR with long‐term administration of tocilizumab had been overall safe and without significant side effects in our hands 30–36 . A recent report by Cabezas et al 35 evaluated the reported an evaluation of published literature from case studies regarding the efficacy of tocilizumab in treating cAMR.…”
Section: Tocilizumab (Anti–il‐6r) For Treatment Of Amrmentioning
confidence: 77%
“…However, boosting endogenous Tregs with immunomodulatory therapies in vivo is an attractive alternative which would eliminate current limitations associated with performing adoptive cell therapy and could be widely clinical applicable. We and others have shown IL‐6 inhibits Treg differentiation and its inhibition with anti–IL‐6/IL‐6R treatment increases Treg numbers in animal models and human studies in vivo 28,32,35,38 . Granofszky et al 41 evaluated treatment with anti–IL‐6 instead of Treg transfer to determine if this would lead to multi‐lineage chimerism in recipients of fully mismatched BMT.…”
Section: Anti–il‐6/il‐6r Therapy: Inducers Of Treg and Breg Cells?mentioning
confidence: 99%
See 2 more Smart Citations
“…Tocilizumab is a highly specific monoclonal antibody that recognizes IL-6R [ 93 ]. Serum levels of IL-6 and soluble IL-6R are elevated in RA patients after treatment with tocilizumab, which is currently approved by the FDA for the treatment of RA and juvenile idiopathic arthritis [ 94 , 95 ]. The effects of tocilizumab in cancer disease are similar to those of RA, with patients receiving tocilizumab experiencing functional IL-6R blockade, increased serum IL-6 and soluble IL-6R levels, decreased levels of phosphorylated STAT3, and more active T-cell function in vivo, secreting more interferon-gamma and tumor necrosis factor-alpha [ 96 ].…”
Section: Stat3 Inhibitors and Cancermentioning
confidence: 99%